RCSI HANDBOOK OF CLINICAL SURGERY FOR FINALS. - Hill, Arnold D. K.; Offiah, Gozie ([Place of publication not identified] : CRC PRESS, 2019)
Developed over three editions by the Royal College of Surgeons of Ireland to support students attending the three RCSI universities, this convenient handbook provides pragmatic guidance to the principles and practice of surgery that students can expect to encounter during undergraduate and early postgraduate studies. Spanning the full range of surgical specialties, information is presented in a convenient and clinically-relevant format that takes the students through the patient journey from presenting symptoms and etiology to investigations, management and follow up. The text, written as easy-to-read and easy-to-remember bullet lists, is supplemented throughout by tables, management algorithms and colour illustrations. Thoroughly updated, this fourth edition is available to customers outside the RCSI universities for the first time. Covering the core surgical knowledge needed to become a safe and competent doctor, the book will be an invaluable companion for clinical placements and during the critical run-up to final examinations.
OCLC-licensed vendor bibliographic record.
Keywords: Surgery -- Examinations -- Study guides; MEDICAL / Surgery / General